Demographic Characteristics and Functional Levels of Patients With Fragility Fractures Who Accept Tele-rehabilitation as an Alternative to Face-to-face Home Rehabilitation. Issue 3 (August 2021) - Morris, Claire; Van den Berg, Maayken; Barr, Chris; George, Stacey; Crotty, Maria
There is a gap in the evidence on telerehabilitation (TR) for people with fragility fractures. It is unclear whether this group with recent falls who are often frail with cognitive changes will accept tele-rehabilitation and functional gains can be achieved using this approach. Prospective observational study of consecutive patients admitted with femoral or pelvic fracture to a hospital-based home rehabilitation service (HRS) between January and November 2017. Using tablets, multidisciplinary rehabilitation was provided via videoconferencing and use of exercise apps. Patients chose a face-to-face visit or TR. Information on demographic characteristics, functional levels, the total number of therapy sessions, TR episodes, reasons for non-acceptance of TR, and patient-reported experience using TR was collected. Fifty-two patients with hip and pelvic fractures were admitted to the HRS and 35 (67.3%) received TR. Patients who did not accept TR were older, frailer and more likely to be female than those who received TR. Of the 17 who did not receive TR, 6 were deemed unsuitable by staff due to hearing, vision or cognitive problems and 3 refused. The TR group achieved acceptable functional gains. In the TR group on average, participants had 13.63 (± 7.29) home visits however they only elected to have 3.43 (± 2.48) sessions delivered via TR. TR was acceptable to a subset of hip fracture patients but face-to-face was the preferred mode of delivery. More research is needed to understand patients' preferences and beliefs, and the influence of clinician attitudes on uptake of TR.